Children hospitalized for myiasis in a reference center in Uruguay - Martín Notejane; Cristina Zabala; Lucía Ibarra; Leticia Sosa; Gustavo Giachetto (Boletín Médico del Hospital Infantil de México, 2021)
Background: Myiasis is an emerging disease caused by tissue invasion of dipteran larvae. In Uruguay, Cochliomyia hominivorax and Dermatobia hominis are the most frequent species. This study aimed to describe the epidemiological and clinical characteristics and the follow-up of children < 15 years hospitalized for myiasis in a reference center in Uruguay between 2010 and 2019. Methods: We conducted a descriptive and retrospective study by reviewing medical records. We analyzed the following variables: age, sex, comorbidities, origin, the month at admission, clinical manifestations, other parasitoses, treatments, complications, and larva species identified. Results: We found 63 hospitalized children: median age of 7 years (1 month–14 years), 68% of females. We detected risk comorbidities for myiasis (33%), of which chronic malnutrition was the most frequent (n = 6); 84% were from the south of the country; 76% were hospitalized during the summer. Superficial and multiple cutaneous involvements were found in 86%: of the scalp 50, furunculoid type 51, secondary to C. hominivorax 98.4%, and to D. hominis in 1.6%. As treatments, larval extraction was detected in all of them, surgical in 22%. Asphaltic products for parasites were applied in 94%, ether in 49. Antimicrobials were prescribed in 95%; cephradine and ivermectin were the most frequent. About 51% presented infectious complications, impetigo was found in 29, cellulitis in 2, and abscess in 1. Conclusions: Myiasis predominantly affected healthy schoolchildren during the summer months and was frequently associated with ectoparasites. Superficial infestation of the furuncle-like scalp by C. hominivorax was the most frequent form. Infectious complications motivated hospitalizations.